Priming with Humic Acid to Reverse Ageing Damage in Soybean [Glycine max (L.) Merrill.] Seeds - Indika Weerasekara; Uma Rani Sinniah; Parameswari Namasivayam; Muhamad Hazim Nazli; Sharif Azmi Abdurahman; Mohd Norsazwan Ghazali (Agriculture, 2021)
Soybean seed vigour declines with increase in storage duration, due to ageing, which can be alleviated through seed priming. The objective of this study was to investigate the effects of Humic acid (HA) priming on germination, vigour and seedling performance under laboratory and greenhouse conditions with two soil moisture level [50% and 80% field capacity (FC)]. Seeds stored for 12 months having 60% germination were primed either with 0.2 g/L HA solution or distilled water (hydro-primed) at 25 °C for 1, 3, 5 and 7 h. Non-primed dry seeds were used as control, giving nine treatment combinations. Various germination traits [mean germination time (MGT), final germination percentage (FG%), germination rate index (GRI), seedling emergence percentage (SEP)], mean emergence time (MET), seedling quality traits [seedling vigor index (SVI), shoot length, root length, root volume], antioxidant enzyme activities [catalase (CAT), peroxidase (POD)], lipid peroxidation [malondialdehyde (MDA)] and electrical conductivity (EC) were determined. A germination test in the laboratory was conducted as single factor (nine priming treatments), while the greenhouse experiment was conducted as two factors [2 soil moisture level (50 and 80% FC) and 9 priming treatments]. The results indicated that seeds primed with HA for 5 h was able to reinstate the CAT activities (25%), POD activities (50%) and reduced EC (51%) and MDA content (40%) compared with non-primed seeds, reduced the MET (from 4.3 to 3.5 days), increased FG% (from 62 to 71%), GRI (15.6–21.1) and SEP (from 35 to 54%) and (from 60 to 72%) at 50% FC level and 80% FC level, respectively. A strong negative correlation (r = −0.80 **) was found between MDA content and GRI, while CAT and POD activities had positive correlation with GRI r= 0.67 ** and r = 0.56 **, respectively. Thus, priming with 0.2 g/L HA for 5 h improved the vigour of minimally deteriorated soybean seeds resulting in increased emergence with more uniform field establishment.